(untitled) (Psicologia USP, 2009)
This paper presents guidelines of the research on childhood in several fields of knowledge and particularly in the social sciences, highlighting how children come to be conceived as social actors and as culture and meaning producers. It is argued that childhood requires interdisciplinary work and flexible research processes, and that the contemporary complexity begs for a rupture of child-adult dichotomies originated in the Modern Age. Though some interdisciplinary studies are already available, the recognition of childhood as a hybrid phenomenon, both biological and social, implies that understanding childhood requires further integration of natural and social sciences research efforts.